1983
DOI: 10.1177/00220345830620010501
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocholinesterase Activity and Its Origin in Human Oral Fluid

Abstract: Pseudocholinesterase (PCE) activity in oral fluid of 31 male and 24 female subjects was determined using butyrylthiocholine iodide as substrate. Males had approximately twice as much salivary PCE activity as did females [4.8 +/- 2.4 (S.D.) U/1 and 2.2 +/- 1.5 (S.D.) U/1, respectively]. The activity was not much affected by salivary flow rate, although in men it was a little higher in stimulated than in unstimulated saliva. Salivary PCE activity showed diurnal variation. Accordingly, activities were about three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…In this study, it was seen that salivary PChE activity was increased in patients with AD compared to the control group. Ryhaneh's result showed no relation of PChE activities in saliva and serum samples . Therefore, the level of enzymes in saliva may be influenced by many local factors and does not show serum level in this disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, it was seen that salivary PChE activity was increased in patients with AD compared to the control group. Ryhaneh's result showed no relation of PChE activities in saliva and serum samples . Therefore, the level of enzymes in saliva may be influenced by many local factors and does not show serum level in this disease.…”
Section: Discussionmentioning
confidence: 90%
“…The color developed from the reaction of enzyme products with DTNB was measured at 412 nm. The Bradford method was used to evaluate saliva protein level …”
Section: Methodsmentioning
confidence: 99%
“…In our study, mean CVs between individuals for the pipette and Salivette ® samples, respectively, were 66 and 77%. Other authors have reported activity equating to interindividual CVs of between 4 and 89% (Abdollahi et al, 1995(Abdollahi et al, , 1996Ryhanen et al, 1983;Ryhanen, 1983;Sayer et al, 2004b;Ueda & Yamaguchi, 1976;Yamalik et al, 1990Yamalik et al, , 1991.…”
Section: Discussionmentioning
confidence: 94%
“…Low levels of cholinesterase activity are also known to be present in human saliva (Abdollahi et al, 1995(Abdollahi et al, , 1996Chauncey et al, 1954;Drjankova & Zaprjanova, 1981;Giddon & Lisanti, 1962;Ryhanen et al, 1983;Ryhanen, 1983;Sayer et al, 2004Sayer et al, , 2004bUeda & Yamaguchi, 1976;Yamalik et al, 1990Yamalik et al, , 1991. In a group of exposed pesticide factory workers, cholinesterase activity in saliva was lower than the activity in healthy controls (Abdollahi et al, 1996).…”
mentioning
confidence: 99%
“…Human cholinesterase consists of acetylcholinesterase and pseudocholinesterase 40) . Acetylcholinesterase was used in this study to investigate the biodegradation of resin at the interfaces.…”
Section: Discussionmentioning
confidence: 99%